The catalytic oxidation process of atrazine by ozone microbubbles: Bubble formation, ozone mass transfer and hydroxyl radical generation. (June 2023) - Liu, Ting; Zhang, Bin; Li, Wenqian; Li, Boda; Han, Ziwen; Zhang, Yanjie; Ding, An; Wang, Shutao; Ma, Jun; He, Xu
Abstract: Ozone microbubbles have received increasing attention since they can produce hydroxyl radical (OH) to decompose ozone-resistant pollutants. Besides, compared with conventional bubbles, microbubbles have a larger specific surface area and higher mass transfer efficiency. However, the research on the micro-interface reaction mechanism of ozone microbubbles is still relatively scarce. Herein, we systematically studied the stability of microbubbles, ozone mass transfer and atrazine (ATZ) degradation through multifactor analysis. The results revealed that bubble size was dominant in the stability of microbubbles, and gas flow rate played a major role in ozone mass transfer and degradation effects. Besides, the bubble stability accounted for the different effects of pH on ozone mass transfer in two aeration systems. Finally, kinetic models were built and employed to simulate the kinetics of ATZ degradation by OH. The results revealed that conventional bubbles could produce OH faster compared with microbubbles under alkaline conditions. These findings shed light on the interfacial reaction mechanisms of ozone microbubbles. Graphical abstract: Image 1 Highlights: The key influencing factors of each oxidation process were investigated. With pH varying, microbubbles and conventional bubbles respond differently. pH influenced the mass transfer of ozone through changing the stability of bubbles. Conventional bubbles had higher .OH generation rate compared with microbubbles at pH 9.